USM-TSU COLLABORATION TO ADVANCE BIOSCIENCE RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – Universiti Sains Malaysia (USM) and Tomsk State University, Russia (TSU) are embarking on crossdisciplinary research in Biopolymers and Biotechnology as agreed in a Memorandum of Understanding (MOU) inked in March 2015.